2012
DOI: 10.1007/s00253-011-3832-z
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-resistant rhizobial bacteria isolated from nodules of leguminous plants growing in high Hg-contaminated soils

Abstract: A survey of symbiotic bacteria from legumes grown in high mercury-contaminated soils (Almadén, Spain) was performed to produce a collection of rhizobia which could be well adapted to the environmental conditions of this region and be used for restoration practices. Nineteen Hg-tolerant rhizobia were isolated from nodules of 11 legume species (of the genera Medicago, Trifolium, Vicia, Lupinus, Phaseolus, and Retama) and characterized. Based on their growth on Hg-supplemented media, the isolates were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…However, many environmental factors, including heavy and transition metals, often limit the potential of symbiotic systems and have negative effects on both growth and nitrogen fixation of rhizobia (13). Recently, many rhizobial strains with enhanced ability to survive in the presence of high concentrations of heavy and transition metals have been isolated from the root nodules of various legumes (14,15). Further studies revealed that the nodulation and nitrogen-fixing ability of metal-resistant rhizobia were not affected by metal ions.…”
mentioning
confidence: 99%
“…However, many environmental factors, including heavy and transition metals, often limit the potential of symbiotic systems and have negative effects on both growth and nitrogen fixation of rhizobia (13). Recently, many rhizobial strains with enhanced ability to survive in the presence of high concentrations of heavy and transition metals have been isolated from the root nodules of various legumes (14,15). Further studies revealed that the nodulation and nitrogen-fixing ability of metal-resistant rhizobia were not affected by metal ions.…”
mentioning
confidence: 99%
“…The isolation and characterization of native rhizobia could lead to improvement in the manufacture of commercial inoculants and crop production. Rhizobial strains can also be used as co-inoculants with plant growth rhizobacteria [8,9] and for bioremediation purposes [18,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental abiotic stresses not only have an injurious effect on metabolism, growth and plant development but also affect the organ of the symbiosis, the nodule (de María et al 2007). The effect of Hg on the Bradyrhizobium-Lupinus symbiosis has been previously investigated (Ruiz-Díez et al 2012a;Quiñones et al 2013 growing in Hg-contaminated soils. Among these isolates, one of them, L7AH, was very tolerant of Hg growing in a liquid culture medium containing 12.5 μM Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds were sown in 1 L autoclaved pots filled with vermiculite moistened with water containing the corresponding Hg concentration (0-200 μM HgCl 2 ). Seeds were inoculated twice (first at sowing and then 1 week later), according to de Lorenzo et al (1994) with 1 ml of the Hgresistant strain L7AH (Ruiz-Díez et al 2012a) or the Hgsensitive strain L3 (Ruiz-Díez et al 2012b) of Bradyrhizobium canariense. Increasing concentrations of HgCl 2 (0-200 μM) were added together with the nutrient solution three times a week and until the end of the experiment (6 weeks), according to Quiñones et al (2013).…”
Section: Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation